2021
DOI: 10.2147/ijnrd.s291319
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury and Progressive Diabetic Kidney Disease: An Epidemiological Perspective

Abstract: Purpose: Diabetic kidney disease (DKD) represents a unique subset of patients with chronic kidney disease (CKD). Acute kidney injury (AKI) is implicated in DKD progression; however, their interplay is not studied well. We studied risk factors for AKI and the effect of AKI on disease progression in a homogeneous group of patients with DKD. Patients and Methods: We conducted a retrospective open cohort study of patients with DKD at a single tertiary care centre between August 2016-August 2019. Patients with a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Patients with DKD were susceptible to severe AKI and usually had a worse prognosis following AKI (163). Advani recently summarized clearly that diabetes may increase the risk of AKI while AKI may increase the risk of CKD in diabetes (164).…”
Section: Acute Kidney Injury (Aki) and Dkdmentioning
confidence: 99%
“…Patients with DKD were susceptible to severe AKI and usually had a worse prognosis following AKI (163). Advani recently summarized clearly that diabetes may increase the risk of AKI while AKI may increase the risk of CKD in diabetes (164).…”
Section: Acute Kidney Injury (Aki) and Dkdmentioning
confidence: 99%
“…Diabetic kidney disease (DKD) is one of the major chronic complications in diabetes mellitus type 1 (DM1) and 2 and is currently the most common cause of the end-stage renal disease (ESRD). DM contributes to approximately 40% of the newly diagnosed ESRD cases in patients each year [ 4 , 5 ]. The pathogenesis of DKD is multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…According to Prabhu et al [22] , there was a correlation between AKI incidence and lower baseline eGFR, and higher proteinuria. With every 1 g rise in proteinuria, they have revealed that AKI risk was increased by 15.8%.…”
Section: Risk Factors For Akimentioning
confidence: 99%
“…Along with dysfunctional immune systems both humoral and cell-mediated, increase neutrophil dysfunction also contributes to an increased risk of sepsis. [22] Sepsis was the primary cause of AKI in a retrospective study done by Prabhu et al [22] In addition, they showed that there was a higher eGFR decline secondary to sepsis-related AKI as compared to other etiologies. Diabetes mellitus has been demonstrated to be an independent risk factor in a recent meta-analysis of sepsis-related AKI.…”
Section: Risk Factors For Akimentioning
confidence: 99%